Quantifying Uncertainties in Global Growth Forecasts - Ohnsorge, Franziska L. (World Bank E-Library Archive, 2016)
This paper presents a procedure to construct an asymmetric fan chart of risks around global growth forecasts. The distribution of risks around global growth forecasts is estimated by weighting information extracted from option pricing and survey-based measures of risk factors of global growth. The weights are estimated using a vector autoregression analysis. The empirical estimates indicate that forecast uncertainty has increased since January 2016, while the balance of risks to global growth has tilted to the downside